HUMAN RESOURCES MANAGEMENT’S TRANSFORMATIONS: TASKS AND WAYS OF SOLUTIONS - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2023)
Generalized fundamental provisions in the field of social technologies, as well as managerial innovations are formed in the domestic tradition and abroad. The construction of management models was carried out from different angles: from the point of view of the labour process, automation and cybersocialization, bureaucracy, social contacts, interactionism, scientific organization of work, general organizational theory (“tektology”), “natural” organization, reflexive management qualities, features of the Precariat and conditions of Deep Tech. And recommendations of practitioners / analysts in the field of IR – HR (industrial relations – human resources), which have united in the Industrial Relations Research Association (IRRA), are taken in the article into account too. Research by specialists conducted on this basis by the IIRA (International Industrial Relations Association) became widely known. Consideration of the issue of social integration and resources of national identity and self-identification, synergistic approaches to management compositions of informational influences are used [1-5]. Meanwhile, there is now a significant drift of fruitful models of leader activity – an essential part of global transformations. After waves of systemic mechanization, automation, and (bio) robotization, human creative abilities come to the forefront of social (in particular, labour) relations. The structures of interests and values are changing. Creative teams are made up of colleagues, not commanders and performers. Hierarchies of authority rather than authoritarianism are formed. And the authority of the team must be earned. Labour – creativity itself becomes a priority value. At the same time, creativity does not tolerate administrative dictates and forced subordination; “thoughts have no subordination.” The dominance of the “sterile class” of bureaucracy, of various supervisors and directives, is akin to the accumulation of shell rock on the hull of a ship – it must be cleaned off, otherwise the ship suffers and its progress slows down. But not only. Failure to achieve declared goals reveals a tree of genuine, directive ones [6-10]. Consequently, the manager is required to be able not only to deeply understand and generate (to have the right to move from the “do it this way” model to the “do it my way”), but also to provide and motivate the team, creating conditions for creativity. Thus, the effectiveness of a leader’s behavior requires significantly greater abilities from him, moreover, substantive and semantic, and not formal, disciplinary abilities. Good reflective skills become an integral part of a leader. Internal regulation, ensuring the expansion of the area of systemic application of everyone’s talents, collective-group balance, as well as hyper-competition, require an emphasis on endogenous options for economic growth, closely related to the characteristics of value-sense complexes that are basic for cultural-civilizational worlds [11-17].